ANALISIS YURIDIS TENTANG PELAKSANAAN PILKADA TAHUN 2020 DI KOTA MEDAN - Shaleh, Arifin (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
The implementation of general elections in Indonesia has undergone changes to the NRI 1945 until now in 2019 there have been many developments, namely: first, since the issuance of the Constitutional Court Decision No. 97/PUU-XI/2013 regional head elections (pemilukada) are no longer included in the electoral regime, but become a regional government regime. Second, the pattern of organizing elections from 1999 to 2014 was carried out separately, between the legislative elections (DPR, DPD, Provincial DPRD, and Regency/City DPRD) with the presidential and vice presidential elections, and also with the regional head elections (pemilukada). Therefore, the author is interested in studying juridically about the implementation of the 2020 Regional Head Elections in Medan City.Based on the results of the review from the perspective of legal certainty in the implementation of the 2020 Pilkada in Medan City, it can be said that it has not fulfilled the principle of certainty, this is due to the absence of strict sanctions in following up on violations in pandemic conditions, as well as the lack of legal parties in regulating the provisions of sanctions for violators. In addition, if viewed from the side of the value of justice, the implementation of the 2020 Pilkada in Medan City also does not meet the value of justice, because there are still findings or cases of violations, both from administrative violations and in the campaign, this is because there are no strict sanctions regulated in applicable regulations. . It is hoped that the government can affirm and renew sanctions for violators in the implementation of regional elections, especially in the city of Medan.